Theory of mind and peer relationships: The role of social anxiety. Issue 2 (28th October 2019) - Ronchi, Luca; Banerjee, Robin; Lecce, Serena
Abstract: Recent research has shown that individual differences in theory of mind (ToM) during middle childhood are linked with individual differences in children's peer relationships. The present longitudinal study investigated this association more deeply, exploring the potential mediating role played by children's social anxiety. We tested a group of 66 children (11.5 years old at Time 1) three times over one year after their transition to secondary school. Over and above language, SES and stability in individual differences, ToM performance shortly after starting secondary school (Time 1) predicted higher peer acceptance, as well as lower peer rejection, one year later (Time 3) via lower levels of social anxiety over time (Time 2). This study extends our knowledge about the links between social understanding and interpersonal relations in middle childhood. The results suggest that ToM may play an important role in children's adjustment when confronting new social contexts.